2021
DOI: 10.3390/agriculture11020123
|View full text |Cite
|
Sign up to set email alerts
|

Stevia rebaudiana (Bertoni) as a Multifunctional and Sustainable Crop for the Mediterranean Climate

Abstract: Stevia rebaudiana (Bertoni) is a promising medicinal and aromatic plant for Mediterranean agroecosystems given its positive agronomic attributes and interesting quality features. It has both food and pharmaceutical applications, since its leaves contain sweet-tasting steviol glycosides (SVglys) and bioactive compounds, such as phenolics, flavonoids, and vitamins. We evaluated the agronomic and qualitative performances of nine stevia genotypes cultivated, in open field conditions, for two consecutive years unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
(59 reference statements)
1
9
0
1
Order By: Relevance
“…Although the changes in the contents of stevioside and rebaudioside A through the different developmental stages were not as drastic as the other steviol glycosides, results obtained from the relative quantification indicated that their contents decrease when the plants entered the flowering stage. The findings from the present study are in agreement with previous reports which stated that the optimal harvesting time for stevia is at the vegetative stage or just before flowering (during the flower bud formation stage), due to the maximum accumulation of steviol glycosides, especially stevioside, rebaudioside A, and rebaudioside C 6,7,40,41 . Considering the fact that the levels of steviol glycosides and also flavonoids are high during the late vegetative stage, i.e., right before budding and during budding, it is reasonable to suggest that these stages are the optimal harvesting times for the local stevia cultivar.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Although the changes in the contents of stevioside and rebaudioside A through the different developmental stages were not as drastic as the other steviol glycosides, results obtained from the relative quantification indicated that their contents decrease when the plants entered the flowering stage. The findings from the present study are in agreement with previous reports which stated that the optimal harvesting time for stevia is at the vegetative stage or just before flowering (during the flower bud formation stage), due to the maximum accumulation of steviol glycosides, especially stevioside, rebaudioside A, and rebaudioside C 6,7,40,41 . Considering the fact that the levels of steviol glycosides and also flavonoids are high during the late vegetative stage, i.e., right before budding and during budding, it is reasonable to suggest that these stages are the optimal harvesting times for the local stevia cultivar.…”
Section: Resultssupporting
confidence: 92%
“…The decrease in the content of steviol glycosides could be attributed due to the maximum accumulation of steviol glycosides, especially stevioside, rebaudioside A, and rebaudioside C. 6,7,40,41 Considering the fact that the levels of steviol glycosides and also flavonoids are high during the late vegetative stage, i.e., right before budding and during budding, it is reasonable to suggest that these stages are the optimal harvesting times for the local stevia cultivar.…”
Section: Metabolite Variation In Stevia Leaves At Different Developme...mentioning
confidence: 99%
“…Stevia breeding aims to produce higher-performing and yielding genotypes [ 28 , 29 ], selecting genotypes capable of adapting to different environmental conditions and characterised by both high levels of secondary metabolites and biomass yield. Therefore, evaluating the genetic variability among different accessions is important for carrying out breeding programmes [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stevia cinsi dünyanın farklı yerlerinde kültürü yapılan sağlık ve gıda sektörü açısından önemli bir endüstri bitkisidir [1]. Stevia rebaudiana Bertoni Asteraceae (Compositae) familyasına ait çok yıllık, otsu, çalı formunda önemli bir tıbbi ve aromatik bitki türüdür [2][3][4]. Yaprak içeriğindeki steviol glikozitler ile karakterize edilen bitki, tatlı yaprak, tatlı ot ve bal yaprak olarak da bilinmektedir [5][6][7].…”
Section: Introductionunclassified